Salt & Storm - Kulper, Kendall (New York : Little, Brown and Company, 2014)
"Sixteen-year-old Avery Roe wants to take her rightful place as the sea witch of Prince Island. When she foresees her own murder, a harpoon boy named Tane promises to help her change her fate and keep her island safe and prosperous, but salvation will require an unexpected sacrifice"--
Young Adult.
Accelerated Reader
1020
Keywords: Fate and fatalism -- Juvenile fiction; Magic -- Juvenile fiction; Witches -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Islands of the Atlantic -- History -- 19th century -- Juvenile fiction; Fate and fatalism -- Fiction; Magic -- Fiction; Witches -- Fiction; Mothers and daughters -- Fiction; Islands of the Atlantic -- History -- 19th century -- Fiction